1982
DOI: 10.1038/bjc.1982.115
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear-cell infiltration in ovarian cancer. II. Immune function of tumour and ascites-derived inflammatory cells

Abstract: Summary.-Mononuclear cell fractions were isolated from blood, ascites and solid tumours of patients undergoing surgery for Stages III and IV PHA responses of patient blood and ascites fractions were about half that of normal blood. Tumour-infiltrating lymphocytes (TIL) were less than 10% as responsive as normal blood. The depressed PHA responses of the TIL were not due to the presence of a suppressor cell population. NK activity of patient blood was less than that of normal blood, but not as much as the asci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
1

Year Published

1982
1982
1990
1990

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 31 publications
0
12
1
Order By: Relevance
“…In general, NK-cell function was markedly depressed in human tumours (Vose et al, 1977a;Totterman et al, 1980;Mantovani et al, 1980a;Haskill et al, 1982b). Specifically cytotoxic T cells have only been detected in a few instances (Vose et al, 1977b;Werkmeister et al, 1979) suggesting that effector-cell function may be difficult to maintain in situ.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, NK-cell function was markedly depressed in human tumours (Vose et al, 1977a;Totterman et al, 1980;Mantovani et al, 1980a;Haskill et al, 1982b). Specifically cytotoxic T cells have only been detected in a few instances (Vose et al, 1977b;Werkmeister et al, 1979) suggesting that effector-cell function may be difficult to maintain in situ.…”
Section: Discussionmentioning
confidence: 99%
“…ADCC Activity of AscM and TuM ADCC assays were carried out against either the K-cell sensitive tumour target SB, or the monocyte-sensitive erythroid CRBC target cell. Previously, we reported that the blood mononuclear-cell fraction of these patients is frequently as active as that of normal donors in both these assays (Haskill et al, 1982b). TuM had significant activity in 2/4 cases against the monocyte-sensitive CRBC target cell (Fig.…”
Section: Suppression Of the Pha Responsementioning
confidence: 99%
See 2 more Smart Citations
“…Functional studies showing depressed proliferative activity in T cells recovered from ovarian cancers implicated tumour inactivation as the cause, or failure of a particular subset to localise at the tumour site (Haskill et al, 1982a). An alternative explanation might be that the predominant T8 + subset contains functionally active suppressor cells (Vose & Moore, 1979).…”
Section: Discussionmentioning
confidence: 99%